The Role of Benjang Art Extracurricular in Improving Civic Disposition as A Citizenship Competency of Students at Triyasa Junior High School, Bandung - Syifa Tri Pahmanda (Jaladri : Jurnal Ilmiah Program Studi Bahasa Sunda, 2025)
Extracurricular activities are often considered supplementary to education. However, behind every movement and rhythm in the art of Benjang lies the power to shape students' character. This study explores how Benjang, a martial art blended with Sundanese cultural values, fosters civic disposition in students at Triyasa Junior High School in Bandung. Using a qualitative approach through case studies, data was obtained through observation, in-depth interviews, and documentation. The results indicate that Benjang not only trains physical abilities but also teaches the values of responsibility, cooperation, solidarity, and nationalism. Students who actively participate show a stronger tendency to demonstrate attitudes as participatory citizens. This activity provides a good alternative space where civic values are practiced, not simply taught.